2019
DOI: 10.1007/s40195-019-00892-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation Behavior of Coated As-Extruded Mg–Sr Alloy in Simulated Body Fluid

Abstract: As-extruded Mg-Sr alloy, a kind of promising biodegradable biomedical material, was coated using micro-arc oxidation and also using a phosphate conversion coating. The corrosion behaviors were investigated using Hanks' solution. The corrosion of the as-extruded Mg-Sr alloy became more serious with increasing immersion time; that is, the corrosion pits became more numerous, larger and deeper. The micro-arc oxidation coating and the phosphate conversion coating were effective in improving the corrosion resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Figure 4 a shows the polarization curves of the microwave-sintered pure Fe and Fe-8Cu. The corrosion potential ( E corr ) and corrosion current density ( i corr ) were evaluated by the Tafel extrapolation method [ 28 , 29 ]. The polarization curve of the microwave-sintered pure Fe had an obvious current platform in the anode region, as shown in Figure 4 a, which indicated that the pseudo-passivation film might be formed on the surface, affecting the corresponding degradation rate [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 a shows the polarization curves of the microwave-sintered pure Fe and Fe-8Cu. The corrosion potential ( E corr ) and corrosion current density ( i corr ) were evaluated by the Tafel extrapolation method [ 28 , 29 ]. The polarization curve of the microwave-sintered pure Fe had an obvious current platform in the anode region, as shown in Figure 4 a, which indicated that the pseudo-passivation film might be formed on the surface, affecting the corresponding degradation rate [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The EDS spectra in Point 1 and Point 2 in Figure 7C confirmed that the regular corrosion layers and the discontinuous white products on the corroded surface of SLMed ZK30-0.2Cu-0.8Cu specimens contained “O, Mg, Ca, and P” and “O and Mg,” respectively. The Ca and P elements were present on the corroded surface, indicating that Ca-P compounds precipitated on the surface of the hydroxide corrosion layers as the corrosion continued[ 31 ]. The EDS spectra of Point 3 in Figure 7A confirmed that the corrosion products on the corroded surface of SLMed ZK30-0.2Cu contained “O and Mg,” similar to the EDS spectra of Point 2.…”
Section: Resultsmentioning
confidence: 99%
“…With the formation of a large number of bubbles on the surface of the metal sample, the metallic luster of the substrate gradually disappears, and a very thin oxide coating is formed [54,55]. During the corrosion process, the internal layer is considered as the main protective layer of the MAO coating, which is a continuous protective screen to prevent charge transfer and subsequent degradation [56]. The holes and microcracks produced in the process of MAO provide a channel for the corrosive medium to enter the substrate and form a local galvanic cell.…”
Section: Discussionmentioning
confidence: 99%
“…The inner layer can provide a very poor physical isolation of the Zn substrate from the corrosive medium at the beginning of immersion [33]. Due to the me- During the corrosion process, the internal layer is considered as the main protective layer of the MAO coating, which is a continuous protective screen to prevent charge transfer and subsequent degradation [56]. The holes and microcracks produced in the process of MAO provide a channel for the corrosive medium to enter the substrate and form a local galvanic cell.…”
Section: Discussionmentioning
confidence: 99%